Construction of a Digital Asset Regulation Framework in Islamic Social Finance: Blockchain Integration for Zakat Transparency and Estate Planning - Muhammad Imamul Muttaqin Arisandi; Bustomi Arisandi; Bahrul Ulum; M. Khodimul Wahib; Kholid Kholid (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the construction of an Islamic digital asset governance framework within the context of blockchain integration for zakat transparency and digital estate planning in Indonesia. The research responds to the growing tension between rapid technological transformation in Islamic finance and the absence of comprehensive sharia-oriented regulatory mechanisms governing crypto assets, decentralized transactions, and digital inheritance systems. Employing a non-empirical juridical-normative method, the study analyzes statutory regulations, DSN-MUI fatwas, comparative international regulatory models, and interdisciplinary scholarly literature concerning Islamic fintech, blockchain governance, and Maqasid Shariah. The findings indicate that existing regulatory approaches remain fragmented because financial supervision, sharia compliance, and inheritance governance operate within disconnected institutional frameworks. Blockchain technology demonstrates significant potential to enhance transparency, accountability, and efficiency in zakat and waqf management through immutable ledgers and automated smart-contract mechanisms, although unresolved cyber risks, speculative volatility, and succession vulnerabilities continue to threaten the principle of hifzh al-mal. The study formulates the Islamic Digital Asset Governance Framework (IDAGF), integrating technical supervision, sharia certification, judicial authorization, and social-finance accountability into a multilayered governance structure capable of harmonizing algorithmic innovation with Islamic legal certainty and sustainable digital financial ethics.